REKONSTRUKSI PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM KUHP NASIONAL: TELAAH KRITIS ATAS UU NO. 1 TAHUN 2023 DALAM PERSEPEKTIF HUKUM PIDANA MODERN - Januar Agung Saputera; Mesa Indra Naiborhu; Enna Budiman; Liza Widjaja; Maman Sudrajat (The Juris, 2025)
This research examines corporate criminal liability under Law No. 1 of 2023 on the Indonesian Penal Code (KUHP) and the urgency of its reconstruction in light of modern corporate crime complexities. Although KUHP 2023 formally recognizes corporations as subjects of criminal law and prescribes applicable sanctions, it lacks specific norms on proving corporate mens rea and the legal relationship between the KUHP and existing sectoral laws (lex specialis). Using a normative legal approach and comparative study of Dutch and United States systems, this article argues that Indonesia’s criminal law remains rooted in an individualistic paradigm, which inadequately accommodates institutional liability concepts such as corporate culture liability and organizational fault. The analysis also highlights inconsistencies between the KUHP’s fault-based liability approach and strict liability mechanisms recognized in environmental and consumer protection laws. Drawing from international models, including principles set forth in the UNCAC and OECD recommendations, the article proposes a reconstruction of corporate liability norms—reformulating corporate mens rea, clarifying the relationship between KUHP and lex specialis, and integrating collective proof mechanisms. These reforms are necessary to establish a more adaptive, integrated, and responsive framework for corporate criminal liability, particularly in addressing transnational economic crimes in the digital era and across strategic sectors.